2020
DOI: 10.1155/2020/1920789
|View full text |Cite
|
Sign up to set email alerts
|

RCAN1 Inhibits BACE2 Turnover by Attenuating Proteasome-Mediated BACE2 Degradation

Abstract: Amyloid-β protein (Aβ) is the main component of neuritic plaques, the pathological hallmark of Alzheimer’s disease (AD). β-site APP cleaving enzyme 1 (BACE1) is a major β-secretase contributing to Aβ generation. β-site APP cleaving enzyme 2 (BACE2), the homolog of BACE1, is not only a θ-secretase but also a conditional β-secretase. Previous studies showed that regulator of calcineurin 1 (RCAN1) is markedly increased by AD and promotes BACE1 expression. However, the role of RCAN1 in BACE2 regulation remains elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Aluminum chloride (Castorina et al, 2010) BACE2 cDNA-containing plasmid transfection (Sun et al, 2005) Docosahexaenoic acid (Bie et al, 2021) Lentivirus-mediated overexpression (Sun et al, 2005;Wang et al, 2020) Leptin (Niedowicz et al, 2013) Lethal-7c (let-7c) microRNA transfection (Liu et al, 2022) Lysine acetyltransferase 8 (KAT8) transfection (Chen et al, 2020) Lysosomal inhibition (Liu et al, 2013) Morphine and S-nitroso-N-acetylpenicillamine (a nitric oxide donor) (Pak et al, 2005) Nsmce1 (murine homolog of NSE1) knockdown (Gong et al, 2020) Oxidative stress (H 2 O 2 ) (Azmi et al, 2015) Regulator of calcineurin 1 (RCAN1, inhibitor of proteasomal degradation) (Qiu et al, 2020) Thy1-BACE2 expression cassette microinjection (Azkona, Amador-Arjona, et al, 2010) Decreasing of BACE2 expression APP-binding benzofuran compounds (Espeseth et al, 2005) BACE2 gene knockout (Dominguez et al, 2005;Sun et al, 2005) CRISPR/Cas9-mediated elimination of BACE2 gene (Alić et al, 2021) Mulberry extracts (Song et al, 2014) Myocyte enhancer factor 2C (MEF2C) knockdown (Ren et al, 2022) Nsmce1 overexpression (Gong et al, 2020) RNA silencing (via small interfering RNA [siRNA]) of the α7 nicotinic acetylcholine receptor (Qi et al, 2013) Transfection of siRNA targeting BACE2 (Basi et al, 2003;Casas et al, 2010;Rochin et al, 2013;Wang et al, 2020) Note: BACE2 cleaves amyloid precursor protein (APP) in a nonamyloidogenic manner, but may also cleave APP at its β-secretase site, promoting the production of Aβ. Because of uncertainty about the role of BACE2 in AD pathogenesis, both overexpression and reduced expression of BACE2 have been accomplished by various approaches in experimental systems.…”
Section: Increasing Of Bace2 Expressionmentioning
confidence: 99%
“…Aluminum chloride (Castorina et al, 2010) BACE2 cDNA-containing plasmid transfection (Sun et al, 2005) Docosahexaenoic acid (Bie et al, 2021) Lentivirus-mediated overexpression (Sun et al, 2005;Wang et al, 2020) Leptin (Niedowicz et al, 2013) Lethal-7c (let-7c) microRNA transfection (Liu et al, 2022) Lysine acetyltransferase 8 (KAT8) transfection (Chen et al, 2020) Lysosomal inhibition (Liu et al, 2013) Morphine and S-nitroso-N-acetylpenicillamine (a nitric oxide donor) (Pak et al, 2005) Nsmce1 (murine homolog of NSE1) knockdown (Gong et al, 2020) Oxidative stress (H 2 O 2 ) (Azmi et al, 2015) Regulator of calcineurin 1 (RCAN1, inhibitor of proteasomal degradation) (Qiu et al, 2020) Thy1-BACE2 expression cassette microinjection (Azkona, Amador-Arjona, et al, 2010) Decreasing of BACE2 expression APP-binding benzofuran compounds (Espeseth et al, 2005) BACE2 gene knockout (Dominguez et al, 2005;Sun et al, 2005) CRISPR/Cas9-mediated elimination of BACE2 gene (Alić et al, 2021) Mulberry extracts (Song et al, 2014) Myocyte enhancer factor 2C (MEF2C) knockdown (Ren et al, 2022) Nsmce1 overexpression (Gong et al, 2020) RNA silencing (via small interfering RNA [siRNA]) of the α7 nicotinic acetylcholine receptor (Qi et al, 2013) Transfection of siRNA targeting BACE2 (Basi et al, 2003;Casas et al, 2010;Rochin et al, 2013;Wang et al, 2020) Note: BACE2 cleaves amyloid precursor protein (APP) in a nonamyloidogenic manner, but may also cleave APP at its β-secretase site, promoting the production of Aβ. Because of uncertainty about the role of BACE2 in AD pathogenesis, both overexpression and reduced expression of BACE2 have been accomplished by various approaches in experimental systems.…”
Section: Increasing Of Bace2 Expressionmentioning
confidence: 99%
“…Importantly, in the AD brain, BACE2 protein levels inversely correlate with higher Braak stages [29], suggesting that low BACE2 levels portends increasing severity of AD. Although why BACE2 expression describes such a trend in the AD brain remains unclear, it is noteworthy that a recent report has identified RCAN1 (regulator of calcineurin 1) to be a regulator of BACE2 expression [30]. In their report, Qiu and colleagues demonstrated that RCAN1 promotes BACE2 expression by inhibiting its turnover by the proteasome [30].…”
Section: Expression Of Bace2 In the Brainmentioning
confidence: 99%
“…Although why BACE2 expression describes such a trend in the AD brain remains unclear, it is noteworthy that a recent report has identified RCAN1 (regulator of calcineurin 1) to be a regulator of BACE2 expression [30]. In their report, Qiu and colleagues demonstrated that RCAN1 promotes BACE2 expression by inhibiting its turnover by the proteasome [30]. Notably, RCAN1 is highly expressed in the human brain and its expression is further increased in aged and AD brains, which BACE2 expression mirrors.…”
Section: Expression Of Bace2 In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient transfections were performed by using PEI-based protocol [14]. The plasmids pRCAN1 and pNFAT used in transfection were obtained from Weihong Song's lab as described previously [5,15].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%